1980
DOI: 10.1111/j.1365-2621.1980.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective assessments of the degree of cooking of potatoes heated by different methods

Abstract: Standard potato slices were heated for various periods of time by three different methods: boiling water, steam under pressure, and a microwave oven. After heating, the internal temperature was measured together with textural characteristics to assess the degree of cooking, using both a taste panel and an Instron 1140 machine.It was found that for a given method of heating the taste panel score is related to the instrumental measurements of rupture load and rupture energy. It was also found that the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Sensory qualities should be the ultimate definition of whether a product is cooked. One of the few studies showing the relationship between sensory qualities during cooking and corresponding quantitative measurements is that of Collison and others (1980) for potato tissue, as shown in Figure 8. They concluded that a cylindrical potato (D = 5 cm, H = 3 cm) heated in boiling water was cooked the best when its center temperature reached 93 °C in boiling water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory qualities should be the ultimate definition of whether a product is cooked. One of the few studies showing the relationship between sensory qualities during cooking and corresponding quantitative measurements is that of Collison and others (1980) for potato tissue, as shown in Figure 8. They concluded that a cylindrical potato (D = 5 cm, H = 3 cm) heated in boiling water was cooked the best when its center temperature reached 93 °C in boiling water.…”
Section: Resultsmentioning
confidence: 99%
“…However, they did not provide time–temperature history during cooking. Therefore, the modulus value corresponding to when cooking is done had to be backed out using the approximate heating conditions of Collison and others (1980). Thus, same‐sized (D = 5 cm, H = 3 cm) cylindrical potato with thermal properties are given in Table 1 and two different kinetic data from Alvarez and others (2001) and Nourian and Ramaswamy (2003) are used, leading to the histories shown in Figure 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This property, resembling many others composed of food texture profiles (Szeczesniak, 1963), can be determined either by sensory analysis using taste tests, and/or estimated by objective, instrumental methods (Scott Blair, 1958); for example, back-extrusion test cell (Kozempel, 1988), the maximum tissue shear force (Harada, Tirtohusodo, & Paulus, 1985), the force required to induce rupture in a uniaxial compression test (Collison, Johnson, Kikiolu, & West, 1980;Verlinden, De Wit, Nys, & De Baerdemaeker, 1992). Relatively few fundamental tests such as uniaxial compression have been reported for cooked potatoes: rupture stress (Rahadjo & Sastry, 1993;Verlinden, Nicolai, & De Baerdemaeker, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Harada et al (1985) characterized the texture of cooked potatoes by the maximum shear force. Collison et al (1980) and Verlinden et al (1995) applied a uniaxial compression test and used rupture force as a measure of potato cookedness. Also nondestructive methods have been used: Blahovec et al (2007) applied a vibration technique to estimate the potato cooking kinetics responsible for softening and found out that the application of this technique is limited to small tubers only.…”
Section: Introductionmentioning
confidence: 99%